INDEPENDENCE RELATIONS STUDENTS AND ROLE OF PARENTS WITH STUDENTS DECISION CLASS X1 IN SELECTING PROGRAMS IN SMA N 1 TULEH MOUNTAIN WEST PASAMAN - Tuti, Eliza; Ramayani, Citra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
This research was motivated by the number of high school students who can not make their own decisions in choosing majors , one reason is the lack of independence of the students so easily influenced by lingkungan.tujuan of this study was to determine the relationship of independence and the role of parents of students with decision x1 grade students in select majors type of research used in this research is ex post facto correlational approach and methods used quantitative methods . The place of research in SMA N 1 Mount Tuleh districts Tuleh Mountain West Pasaman district . As the informant or informants in this study were high school students N 1 Mount Tuleh many as 90 people . Data collection tool used was through a questionnaire , with a sampling Probability sampling techniques . There results showed that the positive and significant relationship between students independence and the role of parents and students in choosing a major decision at SMAN 1 Mount Tuleh . It is evident from the sig < Î± ( 0.000 < 0.05 ) Based on these results , it is recommended that students should be able to be independent , as well as the parents as the people closest to the child should be able to direct and guide the child when the child found it difficult to make decisions.Keywords : selecting majors, studentâs, parent